Role of iron biofortification to improve growth, yield and chemical composition of maize - Mehboob, Usama; Sarwar, Ghulam; Tahir, Mukkram Ali; Noor-us-Sabah; Manzoor, Muhammad Zeeshan (Journal of Pure and Applied Agriculture, 2023)
Mineral nutrient deficiencies are a worldwide problem that is directly correlated with food insecurity. The most common of these is iron (Fe) deficiency as more than one-third of the world’s population suffers from iron deficiency-induced anemia mainly in developing countries. This study was planned to overcome iron deficiency through its biofortification in maize plants. For this purpose, a pot experiment was conducted to monitor efficiency of iron biofortification on maize and soil health. Fe was applied through seed, soil and foliar mode. The experiment had 07 treatments with 04 replicates; T1 = Control, T2 = Seed priming with 1.0% FeSO4 solution, T3 = Seed priming with 2.0% solution of FeSO4, T4 = Addition of 10 kg ha-1 FeSO4 to soil, T5 = Addition of 20 kg ha-1 FeSO4 to soil, T6 = Addition of 1% FeSO4 solution to leaves as spray and T7 = Addition of 2% FeSO4 solution to leaves as spray. Seed priming with Fe solution was done before sowing. Soil treatments were applied one week after sowing. Foliar application of iron was accomplished at 2 stages viz. 30 and 60 days after germination of maize plants. Plant samples were obtained at maturity and analyzed for iron concentration. Soil samples were collected from all the pots and subsequently analyzed for iron concentration. Results depicted that highest N (0.95%), P (0.20%), K (2.06%), Ca (0.2%), Na (0.27%) and Fe (190 ppm) concentration in maize plant was achieved when Fe was applied as foliar application of FeSO4 @ 2 % solution (T7) compared to other treatments. However, soil organic matter (0.90 %), P (8.375 ppm) and K (182.25 ppm) was recorded by the addition of 20 kg ha-1 FeSO4 to soil (T5). Thus, the mode of foliar application of Fe had beneficial effects on nutritional composition in maize crop and soil than soil application and seed priming. © 2022 Department of Agricultural Sciences, AIOU